Educational Model for Cadres and Housewives Against Changes in Family Knowledge and Behavior in Efforts to Prevent Complications of Type II DM in Bunut Wetan Village, Malang Regency - Fiashriel Lundy Lundy; Pudji Suryani; Prima Soultoni Akbar (Humanistic Network for Science and Technology (HNST), 2020)
The prevalence of DM has doubled every year. Therefore, preventive promotional efforts are needed to prevent complications. This study aims to determine the effect of educational models on changes in knowledge and behavior of families in efforts to prevent complications of diabetes mellitus. This research design is a quasi-experimental. The research was conducted in Bunut Wetan Malang. The population in this study were housewives. The sample of research was 45 housewives who were divided into 3 groups. Treatment group 1 was housewives who were given training by health workers, treatment group 2 were housewives who were given training from cadres, and group 3 was the control group. The sampling technique used was purposive sampling. The dependent variable is knowledge and coping mechanisms. The independent variable is the family education model. The collected data were analyzed using paired sample t-test. The results of this study indicate that there is an effective effect on treatment groups 1 and 2 with a significance of 0.000 (p